Peningkatan Pemahaman Konsep Pengukuran Sudut Menggunkaan Pendekatan Pendidikan Matematika Realistik Di Sekolah Dasar - Miranda, Silvia; Fachrudin, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The purpose of the  research is to describe the increase the understanding of the concept of angel measurement using a realistic mathematical education approach in class IV SDN 01 Campago Ipuh Bukittinggi city 2018/2019 academic year. This type of research is classroom action research with qualitative and quantitative approaches. The research subjects were teachers and 26 grade IV students of SDN 01 Campago Ipuh, Bukitttinggi City. The study was conducted in two cycles, the first cycle two meetings and the second cycle one meeting. This is evidenced by the results of the first cycle of planning aspects of the first cycle 78% (B) increased in the second cycle to 92% (AB) an increase of 14%, the implementation aspect of the first cycle teacher 80% (B) increased in the second cycle to 93% ( AB) an increase of 13%, the action aspects of cyclists I 76 (B) increased in the second cycle to 90% increase by 14%, and understanding the concept of the first cycle with an average of 74 (C) and cycle II increased to 87 (AB ) there was an increase of 13.Keyword: